Предмет: Математика,
автор: oxsna
раскройте скобки и упростите выражение 5ab-(ab+(-5ab-(2ab-1)))
Ответы
Автор ответа:
0
незнаю правельно или нет но вот:
в)5ab-(ab+(-5ab-(2ab-1)))=5ab-(ab+(-5ab-2ab+1)))=
5ab-(ab+(-7ab+1)))=5ab-(ab-7ab+1))=
=5ab-(-6ab+1)=5ab+6ab-1=11ab-1
Автор ответа:
0
5ab-(ab+(-5ab-(2ab-1)))=5аb-(ab+(-5ab-2ab+1))=5ab-(ab-5ab-2ab+1)=5 ab-ab+5ab+2ab-1=11ab-1
Похожие вопросы
Предмет: Другие предметы,
автор: ais7164
Предмет: Экономика,
автор: Miliqq
Предмет: Математика,
автор: ruslantanat973
Предмет: Физика,
автор: BustazzTeeh